Specific mesenchymal/epithelial induction of olfactory receptor, vomeronasal, and gonadotropin-releasing hormone (GnRH) neurons - Rawson, N.E (2010)
We asked whether specific mesenchymal/epithelial (M/E) induction generates olfactory receptor neurons (ORNs), vomeronasal neurons (VRNs) and gonadotropin releasing hormone (GnRH) neurons—the major neuron classes associated with the olfactory epithelium (OE). To assess specificity of M/E-mediated neurogenesis, we compared the influence of frontonasal mesenchyme on frontonasal epithelium, which becomes the OE, with that of the forelimb bud. Despite differences in position, morphogenetic and cytogenic capacity, both mesenchymal tissues support neurogenesis, expression of several signaling molecules and neurogenic transcription factors in the frontonasal epithelium. Only frontonasal mesenchyme, however, supports OE-specific patterning and activity of a subset of signals and factors associated with OE differentiation. Moreover, only appropriate pairing of frontonasal epithelial and mesenchymal partners yields ORNs, VRNs, and GnRH neurons. Accordingly, the position and molecular identity of specialized frontonasal epithelia and mesenchyme early in gestation and subsequent inductive interactions, specifies the genesis and differentiation of peripheral chemosensory and neuroendocrine neurons.